2020
DOI: 10.1101/2020.04.29.069591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rapid COVID-19 RT-PCR Detection Assay for Low Resource Settings

Abstract: Quantitative reverse transcription polymerase chain reaction (RT-qPCR) assay is the gold standard recommended to test for acute SARS-CoV-2 infection. It has been used by the Centers for Disease Control and Prevention (CDC) and several other companies in their Emergency Use Authorization (EUA) assays. RT-qPCR requires expensive equipment such as RNA isolation instruments and real-time PCR thermal cyclers, which are not available in many low resource settings and developing countries. As a pandemic, COVID-19 has… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For developing countries or other resource-limited settings where instrumentation is lacking, other cost-sparing testing alternatives are being explored. Arumugam et al demonstrated a proof of principle of an RT-PCR that could be conducted in 12 min using a setup consisting of thin-walled PCR tubes, sous vide immersion heaters/circulators, and an endpoint readout performed with a light-emitting diode (LED) gel-viewing box ( 326 ). Such creative and innovative solutions from industry and academic settings help meet the global needs for SARS-CoV-2 laboratory testing, besides other NAATs rapidly being developed and validated.…”
Section: Laboratory Methods For the Detection Of Sars-cov-2mentioning
confidence: 99%
“…For developing countries or other resource-limited settings where instrumentation is lacking, other cost-sparing testing alternatives are being explored. Arumugam et al demonstrated a proof of principle of an RT-PCR that could be conducted in 12 min using a setup consisting of thin-walled PCR tubes, sous vide immersion heaters/circulators, and an endpoint readout performed with a light-emitting diode (LED) gel-viewing box ( 326 ). Such creative and innovative solutions from industry and academic settings help meet the global needs for SARS-CoV-2 laboratory testing, besides other NAATs rapidly being developed and validated.…”
Section: Laboratory Methods For the Detection Of Sars-cov-2mentioning
confidence: 99%
“…In addition to the marginal cost per sample, for many lower-volume sites, one has to also consider the additional cost of infrastructure and staff training. Low-cost approaches have been advocated for both RT-LAMP and RT-qPCR tests [ 29 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…These range from extremely low-cost ($10) device sets that could be operated even without electricity [ 30 ], to more expensive $300 equipment that can be used to run concurrent tests in 96-well plates and then reading out fluorescent results with a UV source and a smart phone or a tablet [ 29 ]. The appropriate (fixed capital) cost for such instruments depends strongly on the required number of tests to be run at a time, longevity and stable operation of the equipment, and situation-specific factors.…”
Section: Introduction/backgroundmentioning
confidence: 99%